Essentials of Administering Team Foundation Server 2015: Using TFS 2015 to Accelerate Your Software Development - Gauvin, Gary (Apress L. P, 2015)
This book covers the critical as well as the less obvious aspects of managing Microsoft Team Foundation Server 2015 in a variety of development and test environments. Coverage includes basic installation, initial configuration, maintenance, and common trouble shooting techniques, sizing, and performance considerations.Essentials of Administering Team Foundation Server 2015 explains how TFS can help you incorporate source control in your development environment. You'll learn how to set up TFS to match how you develop software.The book covers using TFS in the whole development process, along with practical advice on how to use its features effectively to get up to speed quickly.In addition, the author dives into using TFS in your team covering subjects like setting up accounts for different roles, manage users, and groups--plus what you need to know about TFS security and running a secure team.No discussion of a centralized system like TFS would be complete without learning how to back up and restore it, and the author covers what you will need to know to maintain your TFS including the backup and restore details required to properly plan for disaster recovery.The book details what you need to know about TFS functionality in creating and setting up collections and projects, how to manage the build process with Team Build (including setting it up and deploying build server and agents), using templates to speed up the creation of builds, building multi-platform solutions, and testing.